Pengaruh Lifestyle, Self Control, dan Financial Literacy terhadap Perilaku Konsumsi - Faadhilah, Ghina; Gumilar, Rendra; Nurdianti, Raden Roro Suci (Global Education Journal, 2023)
This research is motivated by problems that occur in KIP-K recipient students majoring in Economic Education class of 2020-2021, Faculty of Teacher Training and Education, Siliwangi University, Tasikmalaya, namely high levels of consumption. The purpose of carrying out this research is to find out the effect of lifestyle, self control, and financial literacy on consumption behavior in KIP-K Economics Education students class of 2020-2021. The method used is a quantitative approach with a survey method, with an explanatory research design (explanatory research design), as well as data collection techniques using data with a questionnaire (questionnaire). The population in this study were students majoring in Economic Education who received KIP-K class of 2020, totaling 45 people and for the class of 2021 there were 49, so the total population was 94 people. Sampling in this study the entire population was used as a sample, using a non-probability sampling technique with saturated sample types. The results showed that life style has a significant influence on consumption behavior in KIP-K students class 2020-2021 with a significance value of less than 5% (0.000 <0.05), also with self control having a significant influence on consumption behavior in KIP-K students class of 2020-2021 with a significance value of less than 5% (0.000 <0.05), as well as financial literacy which has a significant influence on consumption behavior in KIP-K students class of 2020-2021 with a significance value of less than 5% (0.000 < 0.05). Life style, self control and financial literacy have a significant influence on consumption behavior in KIP-K students class 2020-2021, with a significance value of less than 5% (0.000 <0.05).